(untitled) (Моделювання, керування та інформаційні технології, 2019)
We study an iterative differential-difference three-step method for solving system of nonlinear equations, which uses, instead of the Jacobian, the sum of derivate of differentiable parts of operator and divided difference of nondifferentiable parts. The numerical examples illustrate how the methods works.